Impact of nitrogen induced defect dynamics on UV response of diamond photodetectors. (June 2020) - Mohapatra, Sarthak; Sahu, P.K.; Rath, S.; Sahoo, Pratap K.; Varma, Shikha; Narasimha Murty, N.V.L.
Abstract: This work correlates the ultraviolet (UV) current response of single-crystal diamond photodetectors to the lifetimes of nitrogen-induced color centers. Single-crystal diamond photodetectors are fabricated and characterized by optical and electrical measurements. The optical characterizations include Raman spectroscopy, Photoluminescence spectroscopy (PL) and the Time Resolved Photoluminescence (TR-PL) measurements. The electrical characterizations include the capacitance-voltage (C–V), current-voltage (I–V), and UV response current measurements. As observed from the photocurrent studies, the magnitude of the current response rises up to five order in the voltage range ±100V in comparison to the dark condition. The charge carrier dynamics of the dominant color centers contributing to the response have been analysed quantitatively through UV response, PL and TR-PL measurements. TR-PL studies reveal that the faster component of the decay can be associated with the Shockley Read Hall (SRH)- nonradiative recombination which decreases with the increase in nitrogen concentration. The decay period corresponding to the slower component is attributed to the radiative recombination at the color centers. Highlights: Dependance of nitrogen induced color centers on the response of diamond photodetectors. Ultra-violet (UV) current response in diamond photodetectors. Defect Characterization in the diamond bulk using photoluminescence (PL) and Time resolved photoluminescence (TRPL). Correlation between the densities of color centers to the UV current response in diamond photodetectors.